A Finger Amputation Case Caused by Human Bite - Doğan, Kamil Hakan; Artuç, Selahattin; Doğan, Nadire Ünver; Demirci, Şerafettin (The Bulletin of Legal Medicine, 2014)
Bite is a type of wound created with animal or human teeth. Bite wounds created by humans are encountered in situations as fighting, rape, murder and child abuse. Bite marks are usually observed on arms, neck, breasts, body, cheeks and legs. The teeth may penetrate to skin on the areas where bone or cartilage tissue lies underneath skin, and tissue loss may occur. Auricles are most frequent regions that occur tissue loss with bites. Finger amputation occurring with human bite is extremely rare. The case presented in this paper is a 28 years old man. In his medical history, the 3rd finger of his left hand was bitten during a fight two months ago. One centimeter shortness at the end point of the distal phalanx of the left 3rd finger because of tissue loss was found in the examination. In his left hand radiograph, bone defect at the middle part of the distal phalanx of 3rd finger was determined. The case has been discussed by comparing similar cases rarely reported in the literature.Keywords: Forensic medicine, human bite, amputation
Keywords: forensic medicine; human bite; amputation